2022
DOI: 10.3390/s22145420
|View full text |Cite
|
Sign up to set email alerts
|

Aberrated Multidimensional EEG Characteristics in Patients with Generalized Anxiety Disorder: A Machine-Learning Based Analysis Framework

Abstract: Although increasing evidences support the notion that psychiatric disorders are associated with abnormal communication between brain regions, scattered studies have investigated brain electrophysiological disconnectivity of patients with generalized anxiety disorder (GAD). To this end, this study intends to develop an analysis framework for automatic GAD detection through incorporating multidimensional EEG feature extraction and machine learning techniques. Specifically, resting-state EEG signals with a durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 54 publications
(74 reference statements)
1
42
0
Order By: Relevance
“…The increased AP value of beta indicated that the brain activity is in a state of tension and neural nervousness, and the increased FE value indicated increased complexity ( Al-Ezzi et al, 2022 ). Shen et al (2022) has revealed that GAD patients have higher PSD and FE than healthy adults in beta rhythm. In this study, our results further pointed out that Old_GAD has higher anxiety levels and a more complex brain state in the beta rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The increased AP value of beta indicated that the brain activity is in a state of tension and neural nervousness, and the increased FE value indicated increased complexity ( Al-Ezzi et al, 2022 ). Shen et al (2022) has revealed that GAD patients have higher PSD and FE than healthy adults in beta rhythm. In this study, our results further pointed out that Old_GAD has higher anxiety levels and a more complex brain state in the beta rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that different symptoms of psychiatric disorders also show diverse abnormal FC patterns ( Meda et al, 2012 ). For example, GAD reduces FC in frontal and other brain regions ( Shen et al, 2022 ). Patients with SAD have a limbic FC deficit, which is manifested by reduced frontal-occipital connectivity in resting-states ( Xing et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations